2015
DOI: 10.1128/ec.00032-15
|View full text |Cite
|
Sign up to set email alerts
|

The N-Linked Outer Chain Mannans and the Dfg5p and Dcw1p Endo-α-1,6-Mannanases Are Needed for Incorporation of Candida albicans Glycoproteins into the Cell Wall

Abstract: A biochemical pathway for the incorporation of cell wall protein into the cell wall of Neurospora crassa was recently proposed. In this pathway, the DFG-5 and DCW-1 endo-␣-1,6-mannanases function to covalently cross-link cell wall protein-associated N-linked galactomannans, which are structurally related to the yeast outer chain mannans, into the cell wall glucan-chitin matrix. In this report, we demonstrate that the mannosyltransferase enzyme Och1p, which is needed for the synthesis of the N-linked outer chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…In this study we examined the functions of Dfg5 and Dcw1 in biofilm formation and Hog-1 signaling by using the double mutant strains, ES1 and ES195. Using the above C. albicans mutant strains we have previously confirmed that the Dfg5p and Dcw1p mannanases (crosslinking enzymes) function in cell wall biogenesis in C. albicans (Ao et al, 2015). We have also showed previously that the DFG5/DCW1 conditional mutants have a cell separation growth phenotype.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…In this study we examined the functions of Dfg5 and Dcw1 in biofilm formation and Hog-1 signaling by using the double mutant strains, ES1 and ES195. Using the above C. albicans mutant strains we have previously confirmed that the Dfg5p and Dcw1p mannanases (crosslinking enzymes) function in cell wall biogenesis in C. albicans (Ao et al, 2015). We have also showed previously that the DFG5/DCW1 conditional mutants have a cell separation growth phenotype.…”
Section: Discussionsupporting
confidence: 62%
“…5 ul each of the undiluted, 1:10, 1:100, and 1:1000 dilution samples were spotted onto YNB pH7 plates containing one of the following cell wall stress agents: Calcofluor White (20 µg/ml), Caspofungin (0.25 µg/ml), Congo Red (1 µg/ml), 100 µg/ml SDS (100 µg/ml), or Sorbitol (1 M). Concentrations of stress agents were based on MIC values as described previously (Ao et al, 2015;Nikolaou et al, 2009;Heilmann et al, 2013). In addition, just for the 1M sorbitol experiments WT (SC5314), WT (BWP13), ES1 and ES195 were plated in YNB with 5mM methionine and 2 mM cysteine.…”
Section: Cell Hall Stress Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upadhya et al (2016) showed that deletion of the three chitin deacetylase genes of C. neoformans renders strains avirulent. VDAG_09238 was highly similar to dfg5 which encodes a glycosylphosphatidylinositol (GPI)-anchored cell wall a-1,6-mannanase required for the incorporation of glycoproteins into the cell wall (Ao et al, 2015;Maddi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Mannosylation can impact the function, stability, and localization of proteins and can also lead to the cross linking of glycoproteins to polysaccharides in the cell wall. 12 The cell wall is a dynamic structure. It is rigid enough to provide support and protection, yet is malleable enough to allow for growth and differentiation.…”
mentioning
confidence: 99%